2019
DOI: 10.9775/kvfd.2018.21174
|View full text |Cite
|
Sign up to set email alerts
|

Erken Osteojenik Farklılaşma (In Vitro) Süresince Wistar Sıçanlarda (Rattus novergicus) Gingival Medicinal Signaling Hücrelere Post Trombositten Zengin Fibrin Uygulamasının Agrekan Ekspresyonuna Etkisi

Abstract: Platelet Rich Fibrin (PRF) is rich for growth factors which can improve the Gingival Medicinal Signaling Cells' (GMSCs) osteogenic differentiation. Aggrecan is chondrogenic differentiation marker which has a significant role in the early stage of GMSCs' osteogenic differentiation. This study aimed to analyze the expression of Aggrecan post PRF administration on the osteogenic differentiation in vitro. This research is a true experimental study using the post-test only control group design with a simple random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
(31 reference statements)
0
0
0
Order By: Relevance
“…The increase in collagen gene expression induced by PRF was reported in several studies [27,69,75,78,79], typically around the 14th to the 21st day of exposure. Zhao et al [88] observed slight upregulation by PRF in a dose-dependent manner after 14 or 21 days of culture (p < 0.01).…”
Section: The Molecular Effects Of Prf On Differentiation and Minerali...mentioning
confidence: 63%
See 1 more Smart Citation
“…The increase in collagen gene expression induced by PRF was reported in several studies [27,69,75,78,79], typically around the 14th to the 21st day of exposure. Zhao et al [88] observed slight upregulation by PRF in a dose-dependent manner after 14 or 21 days of culture (p < 0.01).…”
Section: The Molecular Effects Of Prf On Differentiation and Minerali...mentioning
confidence: 63%
“…The study by Nugraha et al [67] investigated the effects of PRF on the osteogenic differentiation of GSPCs, identifying a role of the Cbfa1/Sox9 expression ratio in this process, as it positively correlated with the osteogenic markers and the mineralization of GSPCs. Later, another study by this group [69] showed that PRF also increased the expression of aggrecan, a chondrogenic differentiation marker that has a significant role in the early stage of osteogenic differentiation of gingival stem cells, which may contribute to accelerating bone remodeling with an increased expression of alkaline phosphatase and osteocalcin [67,68].…”
Section: Cell-type Related Effects Of Prfmentioning
confidence: 99%
“…This shows that the collagen in gourami fish scales, when used as a scaffold, can bind and store growth factors (Zhang et al, 2011). Growth factors are known to stimulate and increase the expression of SOX9 from day 7 of osteogenic differentiation, which is thus useful for accelerating bone remodeling and cartilage formation (Nugraha et al, 2019).…”
Section: Groupsmentioning
confidence: 98%